An unusual presentation of postauricular swelling: cholesterol granuloma - Singh, Pradeep Kumar; Kumar, Alekh; Nayak, Gajendra (International Journal of Research in Medical Sciences, 2018)
Post auricular swellings are not uncommon encounterances in surgical practice. Common differential diagnosis would include dermoid and lymph nodes. Cholesterol granulomas are cystic swellings formed with a multi-nucleated giant cell reaction to red blood cells’ breakdown products, haemosiderin and cholesterol crystals. Any aerated portion of the temporal bone may develop a cholesterol granuloma; the mastoid air cells are the most common location and are the most common cystic lesion of the petrous apex. This is the first, unique and rare case of post auricular presentation of a cholesterol granuloma. 21-year-old female presented with a painless swelling behind the left ear from last four years. The radiological examination revealed a left-sided, soft-tissue mass extending into the posterior fossa. She underwent a surgical exploration and complete resection was achieved. The histopathological and radiological features were consistent with a cholesterol granuloma. Authors have seen first case of a mastoid cholesterol granuloma presented as a postauricular swelling. This case illustrates the need to consider cholesterol granuloma in daily clinical practice. Otologists should be aware of uncharacteristic invasive cholesterol granulomas of the mastoid, which require aggressive surgical obliteration.